An Examination of Khaje Atabak’s Tomb, a Remained Memorial Monument from Seljuks’ Era in Kerman - Jamshid Roosta (Journal of Universal History Studies)
Seljuks ruled Kerman for almost a century and a half (433-583 A.H.) and left historical monuments in this city. The current study, being a basic examinational research, aims at introducing one of these memorial monuments named Khaje Atabak’s Tomb, while examining the works done to restore its outer façade and also the present condition of this monument. In order to collect the data library results were utilized along with field studies. The research questions include: 1. Who does Khaje Atabak’s Tomb belong to and when exactly has it been built? 2. What are the decorative details used in this monument? 3. What is the present condition of this place? The results of the study suggest that Khaje Atabak’s Tomb has been one of the most beautiful Iranian monuments of the 6th century AH, mainly famous for its diverse decorations and writings of the inscriptions. Brick decorations, Negin tiles, different plaster work with geometric and natural shapes, knotted Kufi inscriptions, thuluth calligraphy, and many more elegant decorations can be seen in this monument. Despite all this beauty, this place has remained unknown and requires substantial restoration, which has kept the writer occupied for a decade.